Old Testament theology - Rad, Gerhard von, 1901-1971 (Harper, 1962)
Professor Gerhard von Rad, of Heidelberg University, is recognized as a truly pioneering figure in biblical studies. In Old Testament Theology he applies the most advanced results of form criticism to develop a new understanding of the Bible. His original approach is here available for the first time in English. The author shows how the Old Testament text grew out of earlier experiences of God's involvement in the life of Israel. The biblical writings witness to the continued activity of God upon his people and the world. Each part of the Old Testament is seen as a particular historical response to God's action. - Jacket flap.